Structurization and models of strategies for neutralizing investment risks in the construction industry - BODIANSKYI, Oleksiy (Ways to Improve Construction Efficiency, 2025)
Investment risks in the construction industry are among the key factors affecting the stability and profitability of projects. They are shaped by economic, political, technological, and legal changes that directly influence the financial outcomes of development companies. Effective risk management is based on their structuring, systematic classification, and the selection of optimal neutralization strategies. A comprehensive approach to risk management allows not only to minimize potential losses but also to increase the investment attractiveness of enterprises. Within construction projects, financial, legal, environmental, technological, and organizational risk models are applied, each requiring targeted control measures. The use of strategies such as insurance, diversification, hedging, establishment of reserve funds, and contractual mechanisms makes it possible to minimize the negative impact of internal and external factors. Applying a systematic approach enables risk analysis at every stage of project implementation – from design to commissioning. Risk modeling based on analytical tools (SWOT, PESTEL, and GAP analyses) increases the accuracy of forecasting and the effectiveness of managerial decision-making. Particular attention is given to the integration of modern information technologies that ensure real-time risk monitoring, resource optimization, and process control. The neutralization of risks in construction has a strategic nature and involves creating the conditions for sustainable industry development. The introduction of innovative management models enhances the financial resilience of enterprises, reduces losses from unforeseen events, and ensures the efficiency of the investment process. The structuring of risks, combined with adaptive neutralization strategies, forms the foundation of a modern construction project management system focused on forecasting, preventive actions, and long-term business stability. This approach strengthens the competitiveness of the industry, builds investor confidence, and increases the attractiveness of the investment market.